Human Resource Development Strategy in the Beef Industry at CV Sakha Muria, Depok, West Java, Indonesia - Ariyo Seto; Mohamad Sam'un; Fatimah Azzahra (Universitas Muhammadiyah Malang, 2024)
CV Sakha Muria, a beef distribution enterprise, has established a robust presence across Java. This research endeavors to delineate and scrutinize the principal determinants of the company, as well as to delineate priority strategies. Employing a descriptive method with a mixed-method approach, primary data was gathered through interviews and questionnaires, supplemented by secondary data extracted from pertinent academic journals and BPS datasets. Purposive sampling was employed, with a sample size of 19 individuals. Data analysis entailed the utilization of the Internal Factors Evaluation (IFE) Matrix, External Factors Evaluation (EFE) Matrix, Internal-External (IE) Matrix, SWOT Matrix, and QSPM Matrix. Findings indicate that the primary internal factor facilitating the work process of employees is the company's facilities, scoring 0.63, while the predominant external factor is the establishment of robust inter-company cooperation, scoring 0.61. The IE Matrix positions the company at V (2.95, 2.93), suggesting a stance of preservation and maintenance. SWOT analysis reveals the company's commitment to skill development, recruitment of technologically literate and highly motivated employees, and ongoing enhancements to the compensation system to sustain employee attraction. Additionally, the company entrusts experienced personnel with supervisory roles, establishes specialized teams to monitor regulatory changes, and mitigate their impact on employee management costs and procedures. The prioritized strategy, as per the QSPM Matrix with a value of STAS (6.95), underscores the imperative of enhancing employee skills in alignment with market dynamics and adapting to regulatory shifts or policy changes.